Greenwashing in the Food and Soft Drinks Industry: Implications on Wellbeing - A Critical Perspective - Donati, Marijana (Global journal of Business and Integral Security, 2024)
This research investigates the impact of greenwashing on human well-being, focusing on consumer awareness, sugar-related consequences, and the influence of social media. The study uses a mixed-method approach involving quantitative methods (online surveys and Web of Science database analysis) and qualitative methods (content analysis) to explore factors such as ingredient list neglect, attraction to sugar addiction, and susceptibility to social media influence. The study reveals the need for clear communication strategies about ingredient information. The analysis of frequently consumed products exposes a prevalence of lower-nutrient items, high processing levels, and a connection between consumption patterns and sugar addiction. The research also examines athlete endorsements in greenwashing practices, revealing potential inconsistencies and contradictions. Athletes such as Cristiano Ronaldo, LeBron James, Neymar, Serena Williams, Ronda Rousey, and Alex Morgan are scrutinised for their associations with brands like Coca-Cola, KFC, Sprite, McDonald's, and others. The study concludes by emphasising the intricate dynamics influencing consumer interactions with ingredient information and the challenges in making informed dietary decisions. It highlights the importance of transparent communication, potential interventions for healthier choices, and responsible marketing practices, especially concerning athlete endorsements targeting vulnerable populations like children and adolescents. This research contributes valuable insights to the ongoing discourse on the repercussions of greenwashing for academia and industry.